Sufi Interpretations of philosophical Sufism Sheikh Hamza Fansuri in the Kingdom of Aceh Darussalam (1496-1903 CE) - Hidayatullah, Ilham; Yusoff, Mohd Yakub Zulkifli Mohd; Alhajj, Thabet Ahmad Abu (QiST: Journal of Quran and Tafseer Studies, 2025)
This study discusses a reconsideration of the type of Sufi interpretation undertaken by the Sheikh of philosophical Sufism, Hamza al-Fansuri, of Aceh Darussalam (1496-1903 CE). He is considered one of the most prominent figures in philosophical Sufism in Southeast Asia who has authored numerous works on Sufi teachings. The researcher uses an inductive approach through a content analysis of Hamza al-Fansuri's three main books: Asrār al-'Arifin, Syarāb al-'Aṣyiqīn, and al-Muntahī. The researcher finds that Hamza al-Fansuri cited several Quranic verses as evidence; forty-five verses in Asrār al-'Arifin, some of which are repeated in his other two books. Thus, the total number of Quranic verses in the three books is fifty-six. The researcher concludes that Hamza al-Fansuri, despite his fame for philosophical Sufism, his approach to interpreting Quranic verses tends toward both allusions (isyari) Sufi interpretation and theoretical (nadhari) Sufi interpretation. He always combines Sharia and truth, and recognizes the apparent (zahir) meaning alongside the hidden (batin) meaning.